2022
DOI: 10.1002/advs.202200059
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of Nanodiamond Quantum Sensors for Biological Applications

Abstract: Measuring certain quantities at the nanoscale is often limited to strict conditions such as low temperature or vacuum. However, the recently developed nanodiamond (ND) quantum sensing technology shows great promise for ultrasensitive diagnosis and probing subcellular parameters at ambient conditions. Atom defects (i.e., N, Si) within the ND lattice provide stable emissions and sometimes spin-dependent photoluminescence. These unique properties endow ND quantum sensors with the capacity to detect local temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 163 publications
(255 reference statements)
0
54
0
Order By: Relevance
“…Quantum sensing offers the possibility of developing a radically new approach to detecting chemical phenomena. , A central part of these efforts is the creation of quantum bits, or qubits, which are quantum objects that can exist in two states simultaneously as a superposition. The superposition states of an ideal quantum sensor are simultaneously extremely sensitive to their local environment and characterized by a long lifetime, the latter indicated by a long coherence time or T 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum sensing offers the possibility of developing a radically new approach to detecting chemical phenomena. , A central part of these efforts is the creation of quantum bits, or qubits, which are quantum objects that can exist in two states simultaneously as a superposition. The superposition states of an ideal quantum sensor are simultaneously extremely sensitive to their local environment and characterized by a long lifetime, the latter indicated by a long coherence time or T 2…”
Section: Introductionmentioning
confidence: 99%
“…To that end, electronic spins often have strong temperature dependences of their electron paramagnetic resonance (EPR) signals owing to changes in structure. For example, the S = 1 nitrogen vacancy center in diamond has a T -dependent EPR signal from lattice expansion/contraction. , However, for open-shell molecules, the utility of that T -dependence is lessened owing to generally fast superposition collapse outside of He (l) -temperature cryostats. Indeed, this trade off appears relatively common for spin systemshigh environmental sensitivity comes at the cost of short-lived spin superpositions.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, NV color centers in ND combined with optically detected magnetic resonance (ODMR) technique can assume a dominating position in thermometry [ 34 ] for biological application. [ 7 , 35 , 36 ] Nevertheless, ODMR measurements protocols are based on microwave irradiation of the samples, which makes this technique more elaborated and requires awareness on the exploitable optical and microwave power providing the required sensitivity without damaging the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Most of their early applications were the fluorescent labeling of biomolecules and cells by taking advantage of their exceptional photostability and low cytotoxicity [5,6]. However, interest in FNDs has shifted in recent years towards biosensing applications [7][8][9]. The quantum state of the electron spin inside an NVC can be determined from the light emitted from the NVC (optically detected magnetic resonance (ODMR)), and ODMR is sensitive to the environment surrounding the NVC [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have achieved unique nanosensing applications using FND quantum sensors [7][8][9]. Fujisaku et al demonstrated that nanodiamonds serve as nanometric pH sensors [11].…”
Section: Introductionmentioning
confidence: 99%